Hard Way to Enhance Service Quality at The Regional Secretariat Organization Bureau of South Sumatera Province: A Qualitative Reports - Hermince Anggelia Agustinne; Alfitri Alfitri; Andy Alfatih; Husni Thamrin (Universitas Muhammadiyah Ponorogo, 2026)
This study examines the Public Service Innovation Development Model in improving service quality at the Bureau of Organization of the Regional Secretariat of South Sumatra Province. Using a qualitative approach with interviews, observations, and documentation, the study finds that while the innovation model is effective, challenges exist in innovation process management, innovator skills, service standardization, and public participation. Supporting factors include visionary leadership, skilled human resources, technological infrastructure, collaboration, and an innovative culture. Inhibiting factors involve rigid policies, budget constraints, lack of evaluation, and minimal public involvement. Efforts to overcome these challenges include enhancing HR skills, forming an innovation team, developing a strategic plan, establishing service standards, and fostering multi-stakeholder engagement. The study highlights the need for a structured and adaptive innovation model to enhance public service quality effectively. Keywords: Public Service Innovation; Innovation Management; Public Participation; South Sumatera Bureaucracy; Public Service Reform;